2021
DOI: 10.1002/prep.202000299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressure on Mechanical Properties of Composite Propellant

Abstract: Composite propellant must possess sufficient structural capability to withstand the various loading conditions. Several attempts are made worldwide to evaluate mechanical properties of composite propellant at different temperatures and strain rates but effect of pressure has not been yet fully elaborated. In the present study, effect of pressure on mechanical properties of composite propellant was evaluated and discussed to obtain the best possible simulation of firing phenomena. The Universal Testing Machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 9 publications
5
19
1
Order By: Relevance
“…Increasing the confining pressure exhibits little impact on the initial modulus of material but prolongs the linear elastic stage of the curve, causing the yield section of the curve to recede, and the maximum tensile and fracture strength of the sample increases by varying degrees. Maximum elongation and elongation at break also increase with environmental pressure, which are different from the results of HTPB propellant [22,23]. This may be caused by the particles' size and compositions [22].…”
Section: Determine the Value Of Each Parametermentioning
confidence: 57%
See 1 more Smart Citation
“…Increasing the confining pressure exhibits little impact on the initial modulus of material but prolongs the linear elastic stage of the curve, causing the yield section of the curve to recede, and the maximum tensile and fracture strength of the sample increases by varying degrees. Maximum elongation and elongation at break also increase with environmental pressure, which are different from the results of HTPB propellant [22,23]. This may be caused by the particles' size and compositions [22].…”
Section: Determine the Value Of Each Parametermentioning
confidence: 57%
“…The wide temperature-gas confining pressure test system was developed by Zhang et al [22], a high-pressure gas was used to form the confining pressure environment, and the temperature of highpressure gas and propellant samples was controlled by convection heat transfer. Bihari et al [23] pointed that the strain capability of HTPB propellant increased as the strain rate at a given pressure increased, and the maximum stress capability was in the pressure range of 4 to 6 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Thence, in recent years, Zhang et al [23] conducted research on the coupled effects of pressure and temperature on Hydroxy-Terminated Polybutadiene (HTPB) propellants, revealing that the tensile stress-strain curves had no apparent dewetting point under superimposed pressure. Bihari et al [24] found that the tensile stress increased with pressure, while the fracture strain almost kept constant. These results indicated that the differences in composition contents and percentages of solid propellants would also cause different performances under confining pressure conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Bihari et al. [24] found that the tensile stress increased with pressure, while the fracture strain almost kept constant. These results indicated that the differences in composition contents and percentages of solid propellants would also cause different performances under confining pressure conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research has been carried out on the tensile and compressive mechanical properties of HTPB propellants in the past period of time [1][2][3][4][5][6]. The effects of temperature and loading speed on the mechanical properties of propellant under uniaxial loading were studied [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%